The Role of Rahmah El Yunusiyah in Educational Transformation: A Literature Review - Rahmayanti, Elsa; Kuswandi, Dedi; Wedi, Agus (Journal of Practice Learning and Educational Development, 2025)
Rahmah El Yunusiyah was a visionary female figure in the history of Islamic education in Indonesia who made significant contributions to the transformation of the education system. This article aims to analyze in depth Rahmah El Yunusiyah’s role in shifting traditional educational paradigms toward a more progressive and inclusive framework based on Islamic values. Through a systematic literature review, this study identifies Rahmah’s educational innovations, including the establishment of Madrasah Diniyah Puteri, the first formal educational institution designed specifically for Muslim women in Indonesia. The findings reveal that Rahmah not only created learning opportunities for women but also formulated a holistic educational approach that encompassed spiritual, intellectual, and social development. Her impact extended to the reform of Islamic education curricula and the empowerment of women during the colonial period and post-independence era. This study concludes that Rahmah El Yunusiyah’s contributions laid a crucial foundation for developing an education system rooted in local wisdom, which remains relevant to the challenges of educational globalization in the modern era.